Anti-fraud Strategy in Tourism Destination Organizations: The Role of Leader Integrity, Ethical Leadership and Trust in the Leader - Anita Carolina; Anis Wulandari (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2024)
Fraud has enormous negative consequences, not only for enterprises but also for stakeholders and society. The study of fraud prevention has increased in importance in determining how businesses' strategies can prevent fraud and what factors influence the effectiveness of fraud prevention strategies. Leaders in an organization that manages tourist attractions have a critical role in preventing fraud. Built on the social exchange theory, this research investigates the relationship between leader integrity, ethical leadership, trust in the leader, and anti-fraud strategy in the tourism sector in Madura Island, Indonesia. Multi-source data was collected from 193 group members aware of the importance of the tourism sector (Tourism Community) in 4 tourism destination organizations across Madura Island, Indonesia. Findings from structural equation modeling confirmed that leader integrity, ethical leadership, and trust in the leader all contribute to a successful anti-fraud strategy. It has also been proven that there is a positive association between leader integrity and ethical leadership, as well as a connection between leader integrity, ethical leadership, and trust in the leader. This research contributes significantly to tourist management by presenting a theoretical model that connects leadership and anti-fraud strategy elements